Theoretical Perspectives and Scopes for Research on Social Movements and Conflicts - Vega Figueroa, Enver (2024)
The importance of recognizing the scope of social theory for the rigorous study of social movements and conflicts from various theoretical perspectives is addressed. This scope is classified into three levels: i) general theories, ii) intermediate scope theories; and, iii) substantive theories. General theories offer broad and abstract theoretical frameworks to understand social phenomena as a whole, such as Marxism and its variants, functionalism, structural-functionalism, systems theory and deconstructivism. Middle-range theories focus on specific areas of study and provide an intermediate level of abstraction, such as social capital theory or social exchange theory. Substantive theories are specific and explain specific phenomena in particular contexts, such as the theory of resource mobilization in social movements. Alternative conceptualizations of social movements and conflicts are presented, and examples of theories are explored according to their scope. It also shows how these theories are applied in research on social movements and conflicts, and what methodologies to use. Furthermore, methodological recommendations are offered to address this social reality effectively, emphasizing the importance of research ethics and the continuous adaptation of theoretical and methodological approaches. Finally, it is highlighted that social theory plays a crucial role in understanding the complexity of social movements and conflicts.